Propionibacteriaium acidipropionici CP 88 dose alters in vivo and in vitro ruminal fermentation characteristics - Levenson, Jonah, author; Engle, Terry E., advisor; Wagner, John J., committee member; Torres-Henderson, Camille, committee member (Colorado State University. Libraries, 2024)
Twelve steers, fitted with rumen canulae were used in a 4 x 4 Latin square design to examine the impact of the direct fed microbial Propionibacteria acidipropionici (PA) on rumen fermentation characteristics. All steers were housed together in one pen equipped with GrowSafe feed intake monitoring stations and one Greenfeed system used to estimate in vivo methane production. Steers were fed a corn silage-based diet throughout the experiment. Treatments consisted of PA administered at: 1) 0.0; 2) 1.0 x 108; 3)1.0 x 109; and 4) 1.0 x 1010 CFU∙animal-1∙day-1. Treatments were administered directly into the rumen as a single bolus dose daily. On day 7 and 14 of each period, rumen fluid was collected from each steer 2 h post treatment administration for VFA analysis and for determining in vitro fermentation characteristics. Following a 14-d washout period, animal treatments were switched, and the experiment repeated. Data were analyzed as a 4 x 4 Latin square design. In vivo propionic acid molar proportions (25.4 vs 23.6±0.24 mM) and total VFA concentrations (125.2 vs 121.3±1.87 mM) were greater (P < 0.05) in steers receiving PA when compared to controls. In vitro DM disappearance (P < 0.05; 63.3% vs 59.2%±1.12) and total VFA (P < 0.05; 147.9 vs 145.2±1.76 mM) were greater and methane (ml/g DMD) lesser (P < 0.04; vs 13.1 vs 15.6±0.11) in fermentation vessels incubated with rumen fluid from animals receiving PA when compared to controls. Dry matter disappearance (P < 0.03) and propionic acid (P < 0.04) increased linearly as dose of PA increased. In vitro total VFA tended (P < 0.08) to increase linearly and methane production tended (P < 0.09) to decrease quadratically in response PA dose. In vivo methane production was similar across treatments. In conclusion, PA addition improved in vivo and in vitro rumen fermentation, gas production, and rumen microbial manipulation.